Environmental Literacy Through Tales of the Archipelago for Early Childhood - Ramdhania, Ammy; Djoehaeni, Heny (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – This study aims to determine the extent to which Indonesian fairy tales help early childhood in environmental literacy. The environmental literacy movement is increasingly being socialized to raise awareness of the importance of maintaining environmental sustainability and natural balance. Through the fairy tales of the archipelago, environmental literacy is introduced to early childhood in a fun way, helping their social-emotional development, skills, and attitudes to care for the environment as early as possible. The richness and diversity of the archipelago provide many benefits for present and future life. Archipelago fairy tales are part of ethnoparenting to perpetuate the richness of the archipelago’s culture and local wisdom.Design/methods/approach – The method used was a qualitative methods, the research describes a descriptive narrative and is strengthened by data in the field obtained through interviews, filling out questionnaires, and direct observation.Findings – The study results show that students who listen to Indonesian fairy tales in class have broad environmental insight and are quickly reminded to behave in environmental care. The children received adequate knowledge, but their skills, attitudes, and understanding were lacking. So they tend to ignore the environment. The following finding is that a group of children who are not interested in the fairy tales of the archipelago does not know the environmental conditions, so it is not easy to behave in environmental care. Meanwhile, children who are enthusiastic about the archipelago’s fairy tales at school and repeat them at home produce children who really appreciate the environment and apply their insights more creatively in their environment.Research implications/limitations – The study took place in an educational institution with 30 students, four educators, and 30 parents. Practical implications – This study hoped that further research will increase environmental awareness with a different approach, involving students’ parents as role models.Originality/value – The study fundamental to help teachers instill environmental literacy in students their students as early as possible through the fairy tales of the archipelago. Paper type Case study